Patient, Physician, and Assessor Blinding in Phase III Randomized Trials in Oncology: A Meta‐Epidemiological Analysis - Gabrielle Brown; Pavlos Msaouel; Avital M. Miller; Ramez Kouzy; Timothy A. Lin; Joseph Abi Jaoude; Ethan B. Ludmir; Alexander D. Sherry (Cancer Medicine)
ABSTRACT Background Blinding mitigates bias in randomized trials and may be especially crucial for surrogate endpoints, such as progression‐free survival (PFS). Here, we characterize utilization of and factors associated with blinding in Phase III oncology trials with PFS primary endpoints. Methods Two‐arm, superiority‐design trials investigating systemic therapy were identified in May 2024 from ClinicalTrials.gov with no date limitation. Trials were required to have a PFS primary endpoint. The study outcomes were the presence of double‐blind designs and blinded independent central review (BICR) for the primary endpoint. Ninety‐five percent credible intervals for binary outcomes were estimated from beta distributions, and multivariable logistic regressions explored associations with trial‐level features. Results After screening, 237 trials were included, enrolling 127,518 patients. A double‐blind design was used in 105 trials (44%, 95% CrI 38%–51%). BICR was used in 111 trials (47%, 95% CrI 41%–53%), including 39 double‐blind trials (16%, 95% CrI 12%–22%). Trials with BICR had higher odds of meeting the primary endpoint (OR 1.84; 95% CI 1.06–3.18; p = 0.03). The PFS assessor identity (central vs. local) or blinding status was not reported in 50 trials (26%, 95% CrI 16%–27%). Trials that met prespecified significance criteria for PFS were more likely to report whether PFS assessors were blinded/unblinded and central/local (OR, 3.05; 95% Cl: 1.60–5.81; p = 0.0007). Conclusions Despite the importance of double blinding in combination with BICR for reducing bias, only a few trials blinded physicians, patients, and primary endpoint assessors. This meta‐epidemiological study illuminates the prevalence of potential assessment biases affecting PFS in Phase III oncology and secondarily emphasizes the need for improved methodology reporting.